Methodological and Didactic Problems of Applying the Principle of Coherence in Teaching Physics - G. G. Yuldasheva. (Zien Journals, 2022)
In this article presented methodical aspects of increase of efficiency of teaching physics in the higher technical educational institutions, and also examines the didactic conditions of use in the educational process to ensure intra-subject continuity between theoretical and practical knowledge
Keywords: method; knowledge; skill; training of technology